Prokaryotic community diversity during bioremediation of crude oil contaminated oilfield soil: effects of hydrocarbon concentration and salinity - Camacho-Montealegre, Celia Marcela; Rodrigues, Edmo Montes; Morais, Daniel Kumazawa; Tótola, Marcos Rogério (Brazilian journal of microbiology, 2021)
Crude oil extracted from oilfield reservoirs brings together hypersaline produced water. Failure in pipelines transporting this mixture causes contamination of the soil with oil and hypersaline water. Soil salinization is harmful to biological populations, impairing the biodegradation of contaminants. We simulated the contamination of a soil from an oilfield with produced water containing different concentrations of NaCl and crude oil, in order to evaluate the effect of salinity and hydrocarbon concentration on prokaryote community structure and biodegradation activity. Microcosms were incubated in CO2-measuring respirometer. After the incubation, residual aliphatic hydrocarbons were quantified and were performed 16S rRNA gene sequencing. An increase in CO2 emission and hydrocarbon biodegradation was observed with increasing oil concentration up to 100 g kg-1. Alpha diversity decreased in oil-contaminated soils with an increase in the relative abundance of Actinobacteria and reduction of Bacteroidetes with increasing oil concentration. In the NaCl-contaminated soils, alpha diversity, CO2 emission, and hydrocarbon biodegradation decreased with increasing NaCl concentration. There was an increase in the relative abundance of Firmicutes and Proteobacteria and a reduction of Actinobacteria with increasing salt concentration. Our results highlight the need to adopt specific bioremediation strategies in soils impacted by mixtures of crude oil and hypersaline produced water.
Keywords: salinita; Sodium Chloride; Hydrocarbonoclastic prokaryotes; Microbial ecology; ropná a plynová pole; chlorid sodný; RNA, Ribosomal, 16S; Microbiota; Hydrocarbons; Carbon Dioxide; Petroleum; ropa; půdní mikrobiologie; Biodegradation; mikrobiota; Community structure; Oil and Gas Fields; Bacteria; oxid uhličitý; Soil Microbiology; uhlovodíky; Salinity; Soil; půda; Hydrocarbon mineralization; RNA ribozomální 16S